2013
DOI: 10.1242/dev.087379
|View full text |Cite
|
Sign up to set email alerts
|

BRG1 promotesCOUP-TFIIexpression and venous specification during embryonic vascular development

Abstract: SUMMARYArteries and veins acquire distinct molecular identities prior to the onset of embryonic blood circulation, and their specification is crucial for vascular development. The transcription factor COUP-TFII currently functions at the top of a signaling pathway governing venous fate. It promotes venous identity by inhibiting Notch signaling and subsequent arterialization of endothelial cells, yet nothing is known about what regulates COUP-TFII expression in veins. We now report that the chromatin-remodeling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
60
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 47 publications
(78 reference statements)
3
60
0
Order By: Relevance
“…In addition, β-catenindependent and -independent pathways might regulate nr2f2 expression, as inhibition of β-catenin/Tcf-mediated transcription suppressed nr2f2 expression in the CV but not in the PCV. Consistent with this, the chromatin remodeling enzyme BRG1 directly promotes murine Nr2f2 expression independently of β-catenin (Davis et al, 2013). Furthermore, it was recently shown that nr2f2 expression in the PCV depends on Sox7 and Sox18 (Swift et al, 2014).…”
Section: Discussionmentioning
confidence: 52%
“…In addition, β-catenindependent and -independent pathways might regulate nr2f2 expression, as inhibition of β-catenin/Tcf-mediated transcription suppressed nr2f2 expression in the CV but not in the PCV. Consistent with this, the chromatin remodeling enzyme BRG1 directly promotes murine Nr2f2 expression independently of β-catenin (Davis et al, 2013). Furthermore, it was recently shown that nr2f2 expression in the PCV depends on Sox7 and Sox18 (Swift et al, 2014).…”
Section: Discussionmentioning
confidence: 52%
“…The mammalian SWITCH/sucrose nonfermentable (SWI/SNF)-like brahma-related gene 1 (BRG1), encoding an ATPase involved in chromatin remodeling, was found to promote the expression of COUP-TFII, and its inactivation resulted in the induction of arterial markers in veins. 52 In the fish, COUP-TFII has been recently reported to be a target of Sox7 and 18. 51 This, however, is in conflict with what was independently reported, whereby the knockdown of Sox7 and Sox18 would reduce arterial differentiation.…”
Section: Corada Et Al Specification Of Arteries and Veins 2375mentioning
confidence: 99%
“…Indirectly, however, NR2F2 expression can be modulated by progesterone in the mouse uterus, through paracrine mechanisms involving epithelial cells and the HH pathway (Lee et al 2006b, Simon et al 2009b. Upstream regulators of NR2F2 expression must also be considered, including brahma-related gene 1 (SMARCA4 (BRG1)), which is a tumour suppressor that normally promotes NR2F2 expression (Davis et al 2013) and is induced by synthetic retinoids (Xu et al 2010). Interestingly, studies on SMARCA4 conditional homozygous mutants show that these mice develop uterine tumours (Serber et al 2012).…”
Section: Nr2f2 and Ctnnb1 In Uterine Fibroidsmentioning
confidence: 99%